A comparison of different Malaise trap types. Issue 6 (17th August 2022) - Uhler, Johannes; Haase, Peter; Hoffmann, Lara; Hothorn, Torsten; Schmidl, Jürgen; Stoll, Stefan; Welti, Ellen A. R.; Buse, Jörn; Müller, Jörg
Abstract: Recent reports on insect decline have highlighted the need for long‐term data on insect communities towards identifying their trends and drivers. With the launch of many new insect monitoring schemes to investigate insect communities over large spatial and temporal scales, Malaise traps have become one of the most important tools due to the broad spectrum of species collected and reduced capture bias through passive sampling of insects day and night. However, Malaise traps can vary in size, shape, and colour, and it is unknown how these differences affect biomass, species richness, and composition of trap catch, making it difficult to compare results between studies. We compared five Malaise trap types (three variations of the Townes and two variations of the Bartak Malaise trap) to determine their effects on biomass and species richness as identified by metabarcoding. Insect biomass varied by 20%–55%, not strictly following trap size but varying with trap type. Total species richness was 20%–38% higher in the three Townes trap models compared to the Bartak traps. Bartak traps captured lower richness of highly mobile taxa but increased richness of ground‐dwelling taxa. The white roofed Townes trap captured a higher richness of pollinators. We find that biomass, total richness, and taxa group specific richness are all sensitive to Malaise trap type. Trap type should be carefully considered and aligned to match monitoring and research questions. Additionally, our estimates of trap type effects can be used to adjust results to facilitate comparisons across studies. Abstract : We tested five common types of Malaise traps, three Townes style traps and two Bartak style traps, in terms of captured insect biomass, species richness, and richness of taxonomic and functional groups. The type of Malaise trap greatly affected estimates of insect biomass, species richness and species composition. In particular, trap shape, rather than size dictated both biomass and species richness. In addition, our results suggest that the trap colour can affect trap catch, with a white‐roofed trap attracting more flower visiting taxa than its all‐black counterpart, increasing trap catch but also possibly introducing a bias by altering the species composition.